Biological synthesis of silver nanopartical from aqueous extract of actiniopterisradiata and evaluation of their antimicrobial activity - B.KOTESWARAMMA; J.KAMAKSHAMMA; S. VARALAKSMI (International Journal of Pharma and Bio Sciences, 2017)
Nanotechnology is now creating a growingsense of excitement in the life sciences especiallybiomedical devices and Biotechnology. Nanoparticles exhibit completely new or improved properties based on specific characteristics such as size, distribution and morphology. The silver nanoparticles have various and important applications. Historically, silver has been known to have a disinfecting effect and has been found in applications ranging from traditional medicines to culinary items. It has been reported that silver nanoparticles (SNPs) are non-toxic to humans and most effective against bacteria, virus and other eukaryotic micro-organism at low concentrations and without any side effects. In the present study green synthesis of silver nanopartiles (SNPs) is prepared by using Aqueous extract of Actiniopteris radiata (pteridophyte) as a reducing, stabilizing and capping agent. The synthesized SNPs are characterized by SEM, TEM with EDAX. Validation of SNPs was performed on 4 bacterial species. For preliminary conformation of SNPs to observe the colour change from light brown to thick brown shows the formation silver nanoaprticles and the further confirmation of synthesized nanoparticles are SNPs. SEM, TEM and EDAX studies shows that the particles are in different shapes(spherical, cubical, triangulars) and having the size between 4 to 30 nms. The EDAX pattern shows the 3.12 weight percentage of silver present in the synthesized sample solution and EDAX studies shows that the particles are mostly crystalline in nature. Further these biologically synthesized nanoparticles were found to be highly toxic against different multi drug resistant bacterial and fungal pathogens. This is the first report on synthesis of SNPs from Actiniopteris radiata was used for synthesis of SNPs and its antimicrobial studies.